Character Design with The Values of Bela Negara for Kindergarten Students in Surabaya - Aileena Solicitor Costa Rica El Chidtian; Mahimma Romadhona; Roziana Febrianita (Future Science)
The younger generation must be inculcated with the ideology of the Pancasila, so they have strong resilience. The biggest threat, namely terrorism and radicalism, lies not only in the aspect of adverse physical attacks, but rather through ideological propaganda attacks that affect patterns of view. Nationalism and State Defense (Bela Negara) insight possessed by the Indonesian people is currently poor. For this reason, awareness and enlightenment are needed from an early age to foster the love of Indonesia Country. This can be initiated early since the school age in kindergarten. However, there has not been any character design in the educational media for the State Defense (Bela Negara) of the kindergarten. For this reason the research on how attractive characters can be designed for kindergarten students is conducted. This research used qualitative methods. Qualitative research is a scientific method of observation to gather non-numerical data. This type of research